JavaScript novice to ninja - Jones, Darren (SitePoint, 2017)
JavaScript is a must-have skill for all web developers. JavaScript: Novice to Ninja is a fun, practical, and comprehensive guide to the modern usage of this deceptively powerful language. Comprehensively updated to cover ECMAScript 6 and modern JavaScript development, the second edition of this step-by-step introduction to coding in JavaScript will show you how to to solve real-world problems, design eye-catching animations, build smarter forms, and develop richer applications. Learn the basics of JavaScript programming: functions, methods, properties, loops and logic Use events to track user interactions Build smarter web forms that improve the user experience Work with the document object model (DOM) and Ajax to dynamicall update your pages Add functionality to your apps using HTML5's powerful APIs Use Test Driven Development methodology to write more robust code Build a complete, working JavaScript quiz app from scratch.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed October 23, 2017)
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)